Compelled to Perform in the 'Oppressor's' Language? Ndebele Performing Artists and Zimbabwe's Shona-Centric Habitus. Issue 4 (4th July 2017) - Ncube, Gibson; Siziba, Gugulethu
Abstract : This article discusses how the deep-rooted Shona hegemony across all fields of cultural practice in Zimbabwe has compelled some Ndebele arts performers to use Shona language in order to appeal culturally to a Shona audience. Ndebele performing artists have been marginalised if they have not produced artistic works that align themselves with Shona-oriented world views. Primarily using a Bourdieu-inspired theoretical framework, we expose Zimbabwe's 'Shona-centric habitus', and how it functions as an unspoken law that devalues non-Shona towns and cities, particularly how it generates self-censorship and self-subordination among some Ndebele artists. Through an analysis of cultural productions by artists of Ndebele origin, this article analyses how power operates, how hegemony is constructed and ultimately how culture is constrained in Zimbabwe.